RESPIRATORY SYSTEM RESPONSE TO IMMERSION IN WATER UNDER STANDARD SWIMMING POOL CONDITIONS - Kabachkova A.V. ,; F. Xiao,; L. Jiao,; Kapitanov S.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the response of the external respiratory system of healthy men to immersion of the whole body in water under standard conditions of a swimming pool. Methods and structure of the study. The experiment involved 10 apparently healthy volunteers of the first mature age (all men). A continuous ergospirometric study was carried out under full immersion in water under standard swimming pool conditions. Results and conclusions. It is shown that being in comfortable conditions of the aquatic environment leads to an increase in the rate of energy consumption. An urgent reaction to full immersion from the cardiovascular and respiratory systems is described. In particular, an increase in oxygen consumption and carbon dioxide release, an increase in the respiratory exchange coefficient and the formation of deep breathing at a constant frequency were recorded.